Mapping the innovation DNA of agribusiness firms: A multi-method analysis of strategic capabilities and performance - Martínez‐Azúa, B. C.; Dias, Á. (Agribusiness)
Innovation is essential for competitiveness in agribusiness facing dynamic environments. This study examines how market orientation, marketing, relational, and social capabilities influence innovation performance. Using data from 751 Spanish firms and a multi-method approach that integrates Structural Equation Modeling (PLS-SEM), Necessary Condition Analysis (NCA), and fuzzy-set Qualitative Comparative Analysis (fsQCA), the research explores linear, non-linear, and configurational relationships. Results show that market orientation, marketing, and social capabilities show significant linear relationships, while relational capabilities exhibit an inverted U-shaped relationship. NCA identifies marketing and relational capabilities as necessary conditions within the SEM framework; however, none meet the strict necessity thresholds under fsQCA. Configurational analysis reveals multiple successful capability combinations, supporting the concept of equifinality. These findings contribute to innovation theory by integrating variance- and set-theoretical approaches, offering a nuanced view of capability orchestration. Practical implications include guidance for managers on capability development and for policymakers aiming to strengthen innovation ecosystems in agribusiness.